Constituency, Imbrication, and the Interpretation of Change-of-State Verbs in isiNdebele - Crane, Thera; Fanego, Axel (Studia Orientalia Electronica, 2020)
This paper describes the interplay of lexical and grammatical aspect with other grammatical phenomena in the interpretation of the aspectual suffix ‑ile (which we analyse as Perfective) in isiNdebele, a Nguni Bantu language spoken in South Africa. Crucial other phenomena include constituency-related factors such as the conjoint-disjoint distinction and (related) penultimate lengthening, along with morphophonological conditions that trigger different forms of ‑ile. These factors appear to interact differently in isiNdebele than they do in closely related Zulu, suggesting two different paths of grammaticalization, which we argue can change the interpretation of markers of grammatical aspect as they interact with lexical aspectual classes.